Removal of Copper from Water System using Moringa oleifera Press Cake - Ali, Eman N. (URUAE, 2016)
Moringa oleifera is a multipurpose tree with most of its parts being useful for a number of applications. This study is carried out to investigate the potential of Moringa oleifera press cake (MOPC) to be used as biosorbent for Cu (II) ions from water system as a natural, environmentally friendly biosorbent. Copper and other heavy metals present in water are harmful and poisonous and need to be removed from water; using natural biosorbent is one of the solutions. The synthetic water with 200 NTU was used in this study to monitor the biosorbent efficiency. The stock solution of copper with different concentration were added to synthetic water and different dosages of press cake was added and the copper concentration before and after addition of the biosorbent was measured using atomic absorption spectrometry (AAS). The residual turbidity was measured as using jar test and reported. The results showed that the Moringa oleifera press cake is reducing the copper concentration up to 53.49%, and turbidity removal up to 75.45%. More research need to be carried out to find the optimum conditions to remove Cu (II) from water.